A Multilevel CFA–MTMM Approach for Multisource Feedback Instruments: Presentation and Application of a New Statistical Model. Issue 1 (2nd January 2016) - Mahlke, Jana; Schultze, Martin; Koch, Tobias; Eid, Michael; Eckert, Regina; Brodbeck, Felix C.
Abstract : Multisource feedback instruments are a widely used tool in human resource management. However, comprehensive validation studies remain scarce and there is a lack of statistical models that account appropriately for the complex data structure. Because both peers and subordinates are nested within the target but stem from different populations, the assumption of traditional multilevel structural equation models that the sample on a lower level stems from the same population is violated. We present a multilevel confirmatory factor analysis multitrait–multimethod (ML–CFA–MTMM) model that considers this peculiarity of multisource feedback instruments. The model is applied to 2 scales of the Benchmarks® instrument and it is demonstrated how measures of reliability and of convergent and discriminant validity can be obtained using multilevel structural equation modeling software. We discuss the results as well as some implications and guidelines for the use of the model.